IMPLEMENTASI KEBIJAKAN AKREDITASI SATUAN PENDIDIKAN ANAK USIA DINI DI KABUPATEN SIGI TAHUN 2017-2022 - Mohammad Hatta A. Rumi; Mohammad Irfan Mufti; Asrifai (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
The Sigi Regency Government issued the Sigi Regent's PERDA Number 10 of 2017 concerning Management of Education Implementation which contains accreditation policies for PAUD units. However, the accreditation achievement of PAUD units in Sigi district from 2017-2022 is only at 29%, the second lowest position of 13 districts/cities in Central Sulawesi. The aim of this research is to describe and analyze what causes low accreditation achievements in Sigi Regency and how to implement the PAUD unit accreditation policy in Sigi Regency in 2017-2022. The method used in this research is a qualitative descriptive method using the Van Meter and Van Horn (1975) policy model implementation approach. The research results show that the implementation of the PAUD unit accreditation policy in Sigi district has not been effective. Based on the results of a study using the 6 aspects of the Van Meter and Van Horn (1975) model, it was found that the standard and policy target aspects were not good, the policy targets only reached 29%, the resource aspect was not good due to the lack of budget for PAUD units and the ability of educational staff. which is still not good, aspects of communication between organizations and activities of implementers are not good due to policies not being conveyed to targets, aspects of the character of implementing agents are not good due to the attitude of implementers who tend to be passive in implementing policies, socio-economic aspects and are not good due to low motivation of targets to following the program policy, the budget, and the low response from the political elite, the disposition aspect is not good because the implementers are not aware of the existence of the accreditation policy.